Problematika Talfīq Mazhab dalam Penemuan Hukum Islam - Fauzi Saleh (Islamica: Jurnal Studi Keislaman, 2011)
It has been commonly argued that the Islamic law is ordained to address and preserve the interest of men. The rules and values of Islamic law are therefore in accordance with the nature of human being. And because the Islamic law is revealed for all season, as it were, it must accordingly be deeply flexible so that it may fit to all time and all space. This paper addresses this notion of flexibility that Islamic law enjoys by arguing that flexibility is a quality that Islamic law should have if it is to survive. But, it moves on, that flexibility is one thing and the ability of Muslim scholars in preserving this flexibility is something else. While by its very nature, Islamic law is flexible the methods and approaches that some Muslim scholars have developed did work on the nerve of this divine law. One of such method is talfīq, in which one would take the views of different scholars to produce a legal dictum. This method is the focus of this paper. It contends that in principle, the method is a result of the absence of the independent mind in the history of Islam. It nonetheless, does serve as a good method to produce a legal premises suitable for certain type of Muslim society. But it does not always work to preserve the flexibility of the Islamic law.